Fictions of Migration in Contemporary Britain and Ireland - Zamorano Llena, Carmen (Springer International Publishing AG, 2020)
Intro – Acknowledgments – Contents – About the Author – 1 Introduction: Migration, Mobility and the Redefinition of National Literatures in a Global Context – A Sense of Order Amidst the Turbulence of Migration – Migration and Changes to Constructs of National Identity – Fictions of Migration in the Redefinition of National Literatures – The Role of National Differences and Postcolonialism in the Emergence of Fictions of Migration – Fictions of Migration and the Cosmopolitan Outlook – Aim and Structure – References – 2 A Cosmopolitan Revision of the Postcolonial
Description based on publisher supplied metadata and other sources
Keywords: Immigrants-Social conditions; Immigrants; Immigrants in mass media; Electronic books